Pengaruh Manajemen Kurikulum Terhadap Mutu Pendidikan Di SDN 15 Sutijo - Arif Aulia Rizki; Darul Ilmi (Education : Jurnal Sosial Humaniora dan Pendidikan, 2023)
This research itself is motivated by the curriculum management that has been implemented at SDN 15 Sutijo. This was of course done to improve the quality of education at SDN 15 Sutijo, because SDN 15 Sutijo itself is a school with the most remote and difficult terrain so there are many things that must be achieved and improved. So, this research itself aims to determine the influence of the management that has been implemented on the quality of education at SDN 15 Sutijo. This research itself is correlation research with a quantitative approach. The population is 11 teachers and 56 students consisting of 6 classes. The sample consisted of 34 students using cluster random sampling. Data was collected via questionnaire and analyzed using a simple linear regression test. The research results showed that curriculum management had an influence on the quality of education at SDN 15 Sutijo. This is proven by the sig value in the hypothesis test of 0.030 < 0.05 and curriculum management influences the quality of education at SDN 15 Sutijo by 46.4%.